BANK INTEREST HALAL: DISTINCTION INTERPRETATION OF CONTEMPORARY ULAMA THOUGHT UMER CAPHRA AND MUHAMMAD SAYYID THANTHAWI - Miftahul Huda; Fikriyyatun Nabila; Isma Fathya Fajriati; Listya Rahmah; Zaimudin Al-Mahdi Mokan (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2022)
Life is controlled by two great forces, namely economy, and religion. All things based on Sharia law are clearly about halal and haram. Bank interest is something that is no longer common among the public, with the law and practice still being debated by some scholars. Therefore, this study aims to answer public confusion about the law of halal interest according to Umer Caphra and Muhammad Sayyid Thanthawi and the reasons for making legal decisions regarding bank interest. The research is in the form of a qualitative method with a literature study using several references from books and journals in concluding the views of the two figures. The primary data used is from the book Prohibition of Interest: Does it make sense? The work of Umer Chapra. While secondary data comes from various books and journals related to bank interest. The results of this study indicate that the two scholars have different opinions regarding bank interest. Umer Chapra argues that the practice of bank interest is prohibited in Islam because usury interest can harm the poor. Meanwhile, Muhammad Sayyid Thanthawi argues that bank interest is not part of usury because bank interest is not part of faith and worship.